2017
DOI: 10.3233/jad-170660
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolism and Survival Across the Frontotemporal Dementia-Amyotrophic Lateral Sclerosis Spectrum: Relationships to Eating Behavior and Cognition

Abstract: A spectrum of changes in lipid metabolism has been identified in ALS-FTD, with total cholesterol levels found to potentially impact on survival. These changes were mediated by changes in fat intake, and BMI, and may also be mediated by the neurodegenerative process, offering the potential to modify these factors to slow disease progression and improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 49 publications
3
34
0
Order By: Relevance
“…Several studies using diverse study populations have been conducted to examine the associations of blood lipids with the survival of patients with ALS. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] While some of the studies reported that higher lipid levels were indicative of longer survival after ALS diagnosis, [19][20][21] which is in line with the present findings, other studies reported a null association between lipids and ALS survival after multivariable adjustments. [10][11][12]14,15 The notable discrepancies among these studies may be attributable to the different study designs used, the varying timing of lipids measurement, and the choice of multivariable adjustments.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Several studies using diverse study populations have been conducted to examine the associations of blood lipids with the survival of patients with ALS. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] While some of the studies reported that higher lipid levels were indicative of longer survival after ALS diagnosis, [19][20][21] which is in line with the present findings, other studies reported a null association between lipids and ALS survival after multivariable adjustments. [10][11][12]14,15 The notable discrepancies among these studies may be attributable to the different study designs used, the varying timing of lipids measurement, and the choice of multivariable adjustments.…”
Section: Discussionsupporting
confidence: 89%
“…[10][11][12]14,15 The notable discrepancies among these studies may be attributable to the different study designs used, the varying timing of lipids measurement, and the choice of multivariable adjustments. For example, most studies recruited patients with ALS from neurology clinics for 2 distinct purposes, namely to investigate the putative risk factors for ALS using a case-control design 9,10,12,18,19,21 or to identify and evaluate potential predictive factors for the prognosis of ALS using a prospective cohort design. 11,[13][14][15]17,20 In the case-control design settings, it is relatively common that not only incident cases but also prevalent cases of ALS were recruited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disentangling pathogenic pathways from compensatory responses will be challenging in future studies as it seems likely that the body tries to adapt to the imbalance of increased energy metabolism by rewiring hypothalamic neural circuits leading to increased food intake 13. An increase in food and fat intake is able to secondarily affect blood lipid levels,14 which in turn have been associated with improved survival 15. As such, it seems likely that ALS may provide an ideal model to study the interaction between energy metabolism, food intake, neurodegeneration and the adaptive mechanisms that try to preserve function.…”
Section: Hypermetabolism May Be Linked To Neurodegenerative Processesmentioning
confidence: 99%